Phosphorylation of the Synaptonemal Complex Protein Zip1 Regulates the Crossover/Noncrossover Decision during Yeast Meiosis. - Xiangyu Chen; Ray T Suhandynata; Rima Sandhu; Beth Rockmill; Neeman Mohibullah; Hengyao Niu; Jason Liang; Hsiao-Chi Lo; Danny E Miller; Huilin Zhou; G Valentin Börner; Nancy M Hollingsworth (PLoS Biology, 2015)
Interhomolog crossovers promote proper chromosome segregation during meiosis and are formed by the regulated repair of programmed double-strand breaks. This regulation requires components of the synaptonemal complex (SC), a proteinaceous structure formed between homologous chromosomes. In yeast, SC formation requires the "ZMM" genes, which encode a functionally diverse set of proteins, including the transverse filament protein, Zip1. In wild-type meiosis, Zmm proteins promote the biased resolution of recombination intermediates into crossovers that are distributed throughout the genome by interference. In contrast, noncrossovers are formed primarily through synthesis-dependent strand annealing mediated by the Sgs1 helicase. This work identifies a conserved region on the C terminus of Zip1 (called Zip1 4S), whose phosphorylation is required for the ZMM pathway of crossover formation. Zip1 4S phosphorylation is promoted both by double-strand breaks (DSBs) and the meiosis-specific kinase, MEK1/MRE4, demonstrating a role for MEK1 in the regulation of interhomolog crossover formation, as well as interhomolog bias. Failure to phosphorylate Zip1 4S results in meiotic prophase arrest, specifically in the absence of SGS1. This gain of function meiotic arrest phenotype is suppressed by spo11Δ, suggesting that it is due to unrepaired breaks triggering the meiotic recombination checkpoint. Epistasis experiments combining deletions of individual ZMM genes with sgs1-md zip1-4A indicate that Zip1 4S phosphorylation functions prior to the other ZMMs. These results suggest that phosphorylation of Zip1 at DSBs commits those breaks to repair via the ZMM pathway and provides a mechanism by which the crossover/noncrossover decision can be dynamically regulated during yeast meiosis.